Muscle strengthening and increasing the articular amplitude of the person submitted to total knee arthroplasty - João Manuel Leitão; Carla Vigia; Ana Cristina Mesquita; Helena Pestana (Associação Portuguesa dos Enfermeiros de Reabilitação, 2022)
Introduction: Goonarthrosis is characterized by the wear of the articular cartilage of the knee and is manifested by disabling pain, joint stiffness and muscle atrophy. Total knee arthroplasty is a possible treatment, which aims to alleviate pain, improve joint range and functionality. However, it requires a rehabilitation plan that includes a set of therapeutic interventions in order to provide muscle strengthening and increase the range of motion of the knee, ensuring independence in life activities and improving the person's functionality. Objective: To identify the impact of rehabilitation nursing care in terms of muscle strength and joint range of motion in a person undergoing total knee arthroplasty. Methodology: Case study that complies with the CAse REport guidelines, in which the case of a person undergoing total knee arthroplasty is presented. The Medical Research Council modified muscle strength scale, goniometry, Barthel Index and Timed up and go test were used as assessment instruments. Results: There were gains in increasing the range of motion of the knee from 55º to 85º, in muscle strength of the hip and left knee joint segments, and in the person's functional independence, obtaining a total score of 95 in the Barthel Index and a time of 38 seconds in the Timed up and go test. Conclusion: The implemented rehabilitation plan contributed beneficially to the recovery of the person undergoing total knee arthroplasty.